PENINGKATAN KUALITAS PROSES PRODUKSI DENGAN PENERAPAN GOOD MANUFACTURING PRACTICES (GMP) DAN WORK IMPROVEMENT IN SMALL ENTERPRISES (WISE) PADA INDUSTRI KECIL DAN MENENGAH BIDANG PANGAN - Nofriani Fajrah; Muhammat Rasid Ridho (JURNAL REKAYASA SISTEM INDUSTRI, 2026)
The Small and Medium Industries (SMEs) sector in Batam City, particularly in the food processing sub-sector, plays a strategic role in supporting regional economic growth and job creation. However, many SMEs still face production quality problems related to sanitation, non-ergonomic work environments, weak process control, and low worker discipline in implementing hygiene standards. These conditions may reduce product quality, productivity, and consumer trust. This study aims to analyze priorities for improving production process quality through the implementation of Good Manufacturing Practices (GMP) and Work Improvement in Small Enterprises (WISE) in food-processing SMEs in Batam City, as well as to develop a practical priority improvement model that can be used as a reference for similar enterprises. This research employed a case study approach using observation, interviews, documentation, and literature review as data collection techniques. GMP and WISE indicators were structured into criteria and sub-criteria, then analyzed using the Analytical Hierarchy Process (AHP) to determine the ranking of improvement priorities. The results show that the main priority criterion is Hygiene and Sanitation Program (46%), followed by Production Process Control (23%), Packaging, Storage and Material-Equipment Handling (11%), Organization of Work (11%), Workplace Design (6%), and Welfare Facilities (3%). At the sub-criteria level, the most dominant factors are First Aid Equipment (58%), Pest Prevention and Control Program (46%), Employee Habits (46%), and Documentation and Record Keeping (39%). The consistency ratio met the acceptable threshold, indicating that the judgments were consistent and reliable for decision-making purposes. The outputs of this study include a priority map for production quality improvement based on GMP-WISE and an AHP-based decision framework that helps SMEs allocate limited resources to the most critical improvement areas. The contribution of this study to knowledge development lies in strengthening an integrative approach that combines food safety, work ergonomics, and decision support systems to enhance the competitiveness of food-processing SMEs in a systematic, measurable, and applicable manner